计算:3/7*5/13-(9/14-3/14)*(-11/13)-3/7*3/13
人气:253 ℃ 时间:2019-12-01 14:38:21
解答
3/7*5/13-(9/14-3/14)*(-11/13)-3/7*3/13
=(5/13-3/13)*3/7-6/14*(-11/13)
=2/13*3/7+3/7*11/13
=(2/13+11/13)*3/7
=3/7
推荐
猜你喜欢
- 有don't do sth instead of doing的用法吗,怎么翻译?
- A successful team beats with one heart是什么意思
- he often___(relax) half a day
- 用作图法求直线斜率时,必须采用什么方法?
- Edward Smith is _____old.He works in a bank.
- 连词成句 threw,Li,Ming,the,ball,another,boy,to
- Lily doesn't want to buy__same present__Lucy did填空
- 麻烦您了,您帮我看看这道题呗 we see things by our eyes对么?为什么